1986
DOI: 10.1128/jvi.57.2.539-546.1986
|View full text |Cite
|
Sign up to set email alerts
|

Properties of the simian virus 40 (SV40) large T antigens encoded by SV40 mutants with deletions in gene A

Abstract: The biochemical properties of the large T antigens encoded by simian virus 40 (SV40) mutants with deletions at DdeI sites in the SV40 A gene were determined. Mutant large T antigens containing only the first 138 to 140 amino acids were unable to bind to the SV40 origin of DNA replication as were large T antigens containing at their COOH termini 96 or 97 amino acids encoded by the long open reading frame located between 0.22 and 0.165 map units (m.u.). All other mutant large T antigens were able to bind to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
35
0

Year Published

1986
1986
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 41 publications
4
35
0
Order By: Relevance
“…A large number of amino-terminal T mutants which are either partly or fully defective for transforming activity have been identified (6,12,21,34,35,37,38,42 shown that these mutants fail to transform cells to anchorage-independent growth (3). Taken together, the results suggest that the 105-to-115 segment constitutes a functional domain devoted to T transforming function.…”
mentioning
confidence: 99%
“…A large number of amino-terminal T mutants which are either partly or fully defective for transforming activity have been identified (6,12,21,34,35,37,38,42 shown that these mutants fail to transform cells to anchorage-independent growth (3). Taken together, the results suggest that the 105-to-115 segment constitutes a functional domain devoted to T transforming function.…”
mentioning
confidence: 99%
“…The host range mutants, which map to the C terminus of T antigen (16,17,50,51,64), produce stable, truncated T antigens and replicate to near wild-type levels (12,50 gradient fractionation. In these SDS gels, every other gradient fraction was precipitated with anti-SV40 antibody recognizing VPI and T antigen.…”
Section: Discussionmentioning
confidence: 99%
“…All T antigen functions required for viral DNA replication, transcriptional control, and neoplastic transformation are localized to the N terminus and middle portion of the protein (12,17,60,67). The role of the C terminus of T antigen (amino acids 660 to 708) in lytic growth of SV40 has been less well understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…T antigen is a 708-amino-acid multifunctional protein that possesses several biochemical activities, some of which map to discrete domains that can act independently of the rest of the polypeptide (18,45). For example, the binding of T antigen to specific sequences within the viral origin of DNA replication is mediated through its DNA binding domain (amino acids 135 to 249), while residues 371 to 625 are sufficient for ATP binding and hydrolysis (1,9,10,18,52). In some cases, proper T-antigen function requires the coordinated action of multiple domains.…”
mentioning
confidence: 99%